2017
DOI: 10.18632/oncotarget.17850
|View full text |Cite
|
Sign up to set email alerts
|

Role of the inflammasome in chronic obstructive pulmonary disease (COPD)

Abstract: Inflammation is central to the development of chronic obstructive pulmonary disease (COPD), a pulmonary disorder characterized by chronic bronchitis, chronic airway obstruction, emphysema, associated to progressive and irreversible decline of lung function. Emerging genetic and pharmacological evidence suggests that IL-1-like cytokines are highly detected in the sputum and broncho-alveolar lavage (BAL) of COPD patients, implying the involvement of the multiprotein complex inflammasome. So far, scientific evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 72 publications
2
87
0
1
Order By: Relevance
“…Trials of low‐dose macrolides have demonstrated clinical benefit with a reduction in pulmonary exacerbations, increased time to next exacerbation and improved quality of life. Patients who are not actively smoking appear to gain greater benefit, possibly reflecting persistence of autoinflammation in the absence of a primary trigger , . These data support the notion that COPD is towards the autoinflammatory end of the IDC and that established COPD has an intrinsic priming of the innate IL‐1 β cytokine pathway.…”
Section: Chronic Obstructive Pulmonary Diseasesupporting
confidence: 61%
“…Trials of low‐dose macrolides have demonstrated clinical benefit with a reduction in pulmonary exacerbations, increased time to next exacerbation and improved quality of life. Patients who are not actively smoking appear to gain greater benefit, possibly reflecting persistence of autoinflammation in the absence of a primary trigger , . These data support the notion that COPD is towards the autoinflammatory end of the IDC and that established COPD has an intrinsic priming of the innate IL‐1 β cytokine pathway.…”
Section: Chronic Obstructive Pulmonary Diseasesupporting
confidence: 61%
“…Oxidative stress and inflammation are two closely related conditions. Indeed, the overproduction of ROS triggers NF-κB and histone acetyltransferase activation, promoting the expression of inflammatory genes and consequently the production of inflammatory cytokines [49].…”
Section: Cigarette Smoke and Biomarkers Inflammationmentioning
confidence: 99%
“…[5][6][7][8] Some diseases are congenital, such as cystic fibrosis, whereas others can be acquired through smoking, such as COPD. 9,10 Lung transplantation is an established intervention for patients with advanced and life-threatening respiratory disease for which standard medical treatment is no longer effective or for which there is no effective standard medical treatment. 11 Three diseases that often necessitate lung transplantation are COPD, interstitial lung disease, and cystic fibrosis.…”
Section: Introductionmentioning
confidence: 99%